Modal response of all-composite corrugated sandwich cylindrical shells. (12th August 2015) - Yang, Jin-Shui; Xiong, Jian; Ma, Li; Feng, Li-Na; Wang, Shu-Yang; Wu, Lin-Zhi
Abstract: A series of all-composite axial and circular corrugated sandwich cylindrical shells is manufactured using a novel hot press moulding method. Modal testing is conducted to investigate vibration characteristics of such composite corrugated sandwich cylindrical shells with free–free boundary condition. In order to predict the structural vibration damping, a finite element model combined with modal strain energy approach is developed, which is adequately consistent with the experimental results. It is shown that the first several orders of vibration mode shapes are dominated by circumferential lobar modes. Circular corrugated sandwich cylindrical shells generally possess higher natural frequencies and damping loss factors than axial corrugated sandwich cylindrical shells since circumferential stiffness and damping capacity of the former are higher than those of the latter. Furthermore, the influence of the corrugated inclination angle, sandwich core thickness and different topological corrugated cores on the structural vibration and damping performances are thoroughly investigated, which might be helpful to guide the manufacturing and dynamic analysis of lightweight cylindrical shells in engineering.